Pemetaan Karakteristik Permukiman Kumuh Pesisir Untuk Pengelolaan Bencana di Makassar (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
Makassar is one of the cities that most of the region is an area of ​​coastal settlements.But climate change is happening constantly in the coastal settlements, causing floods, high winds and waves of the flood, which at any moment threatens homes located area of ​​coastal settlements. This will affect the economic viability and sustainability of life in the region. The purpose of this study was to identify the characteristics of coastal settlements for disaster management in the coastal area of ​​the city of Makassar, so that life can continue. Generally, this research is descriptive-evaluative using two approaches, Behaviour and Architectural Approach Appproach(Neer,1999).The first approach deals with the study of the process of resettlement of residents, "survival strategy" that is owned by a resident that is manifested in the socio-economic conditions.The second approach deals with the study of the housing and settlement patterns.Both approaches operationalized by comparative perspective, by comparing the existence of the settlements were filtered through mechanisms for determining the characteristic typology of settlements. The results showed that the characteristics of slums tend to cluster and spread irregularly. Society naturally put his house directly opposite the beach, with the livelihoods of some fishermen, so the houses are put spread erratically.This will be reorganized based on the structure of the existing regional chamber. Then it will be developed in accordance with the standard arrangement of the waterfront district / waterfront city regulations. From these characteristics will produce a model of disaster management in the coastal area of ​​Makassar.